PENGELOLAAN PEMBELAJARAN KKPI BERBASIS BUKU ELEKTRONIK (Studi Situs di SMK Negeri 1 Pedan Klaten) - WINOTO , MUHAMMAD SIGIT (2011)
The purpose of this research is to describe the characteristics of management computer skills and information management learning based on electronic books in Vocational High School of State 1 Pedan. In particular, this study divided into three objectives: 1) Describe the characteristics of materials computer skills and information management learning based on electronic books in Vocational High School of State 1 Pedan; 2) Describe the characteristics of the classroom environment computer skills and information management learning based on electronic books in Vocational High School of State 1 Pedan; 3) Describe the characteristics of interaction computer skills and information management learning based on electronic books in Vocational High School of State 1 Pedan. This is qualitative research and used ethnography approach. The study was conducted in class XI F Expertise Software Engineering Program of Vocational High School of State 1 Pedan Klaten. Data were collected by observation, interview and documentation. To obtain the data in the research used depth interviews, observation, and documentation. To analyze the data in this problem, the authors use the model data analysis are arranged in the site for description. The results of research are: 1) Material computer skills and information management based on teaching materials in the form of electronic books from VEDC Malang. The material consists of 9 modules close source that is: typing 10 fingers, identify the PC windows, operate the computer peripherals, process words with Microsoft Word, spread sheet processing with Microsoft Excel, create presentations with Microsoft PowerPoint, create a database with microsoft access, how to connect your Internet and working with the Internet via OS windows and theories related to the management of information. Open source material consists of 6 modules, namely: how to identify and operate a computer with linux, open office word processing with writer, create spread sheets with open office calc, made a presentation with Open Office Impress, create a database with open office base and connect the computer with Internet and work with the internet via linux OS. Utilization of electronic books in Vocational High School of State 1 Pedan still focused on the material source close modules namely: Ms learning. Word for word processing, Ms. Excel spread sheet to process and Ms, Powerpoint to make presentations. 2) learning classroom environment computer skills and information management based on electronic books in Vocational High School of State 1 Pedan use the computer labs 10 x 8 m2 , there were 21 PCs plus tables and chairs, air conditioning, LCD projector, white board, bag and shoe rack, lights and windows. Far from the crowds, clean, and sunlight can enter the room; 3) During the process of teaching and learning activities take place, the model of interaction between students and teachers conducted by using the concept that teachers do approach to the delivery of material, then the teacher gives students the opportunity to appreciate how the concept processed. Model of student interaction with students occurs through group discussion model. The model of student interaction with the material occurs when the student opened, read, understand and practice the content of the material.